PENGARUH STUDENT TEAMS ACHIEVMENT DIVISIONS BERBANTUAN MEDIA AUDIO TERHADAP KETERAMPILAN MENYIMAK CERITA ANAK DI KELAS V SDN 10 PONTIANAK - Nurmita Nurmita; Abdussamad Abdussamad; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe problem in this research was “How does the effect of model cooperative learning type of student teams achivement devisions assisted by audio media toward to the listening skills of childrens stories of fifth grade student of Public Elementary School 10 Pontianak Timur ?”. the model used in this study was an experimental method to form the study was Quasi Experimental Design, with experimental design Nonequivalent Control Group Design. The sampling technique used non probability sampling with purposive sampling type. Data collection tools used in the form of learning outcomes document and of a written objective-shaped test with 45 questions. Based on statistical calculations of the final test experimental class average of 71,06 and learning results of final test control class 60,42, the final test data was obtained at 4,551 and (α = 5% dan dk 35 + 25 – 2 = 58) amounting to 1,672, because (4,551) > (1,672), from the calculation of the effect size (ES), was obtained at 0,9689 (big criteria). Then Ha is received. This means that the use model cooperative learning type of student teams achivement devisions assisted by audio media has a high influence on the listening skills of childrens stories of fifth grade Public Elementary School 10 Pontianak Timur . Keyword: Audio Media, Cooperative Learning, Student Team Achivement Divisions, The Listening Skills of Childrens Stories